2021
DOI: 10.3389/fvets.2021.601878
|View full text |Cite
|
Sign up to set email alerts
|

Animal Health Service Delivery in Crop-Livestock and Pastoral Systems in Ethiopia

Abstract: Livestock diseases are a priority problem for livestock keepers throughout Ethiopia. Livestock keepers have also singled out poor animal health service delivery, which is largely the domain of the public sector, as the major constraint to improving animal health and productivity. In the current study, we describe the animal health service delivery system and compile from five questionnaire surveys involving 4,162 livestock keepers to characterize animal health service delivery in Ethiopia. The mapping of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…The economy of Ethiopia is mostly depending on the livestock next to the crop production. Ethiopia is crucial for guaranteeing food security, traction power, rural income production, household employment, and national economic growth through foreign exchange revenues, but it is also significant culturally [3].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The economy of Ethiopia is mostly depending on the livestock next to the crop production. Ethiopia is crucial for guaranteeing food security, traction power, rural income production, household employment, and national economic growth through foreign exchange revenues, but it is also significant culturally [3].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The project responds to a recently published work by Gizaw et al ( 62 ), which assessed veterinary service delivery in Ethiopia, by demonstrating a model for development of services that can work for marginalized mule–muleteer communities in urban settings. The work by Gizaw et al and this project highlight the need for a study of appropriate veterinary service design and community facilitation skills within the curricula of veterinary training institutes to ensure animal health and welfare professionals' awareness of the different approaches that can be used to achieve improved health and welfare for animals, particularly in resource-poor or otherwise marginalized communities.…”
Section: Discussionmentioning
confidence: 97%
“…The project is applicable not only to other cities in Ethiopia with endemic EZL but also to animal healthcare challenges in other circumstances, including other countries with EZL ( 62 ). Successful replication requires recognition of the time needed to build the project on a secure foundation of stakeholder engagement from community to regulatory level.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study showed that mixed crop-livestock farmers had a better KAP score than pastoralists. Mixed crop-livestock farmers have better access to extension and veterinary services which enable them to have a better awareness of animal care and management and implement animal health-related activities than pastoralists ( 37 ). This may in part explain the geographical differences.…”
Section: Discussionmentioning
confidence: 99%